2021
DOI: 10.1051/0004-6361/202140848
|View full text |Cite
|
Sign up to set email alerts
|

In-depth investigation of the physical origin of the soft X-ray excess in PG 1448+273

Abstract: We present systematic X-ray spectral and variability analyses for the narrow-line Seyfert 1 galaxy (NLsy1), PG 1448+273, using the data from two long-exposure XMM-Newton observations of the source in the different flux states. These X-ray spectral analyses indicate that the two main-stream models of soft X-ray excess, the relativistically smeared reflection scenario and the warm corona scenario, show a similar statistical fit to the data sets. However, the warm corona scenario requires a black hole mass that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…the height of corona) is highly variable. Indeed, Ding et al (2021) conducted an in-depth study on the nature of soft X-ray excess and variability of this source by using the multi-epoch XMM-Newton observation data. The results show that the soft X-ray excess of the source is most likely to be originated by the relativistically smeared reflection scenario.…”
Section: Excess Variance Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…the height of corona) is highly variable. Indeed, Ding et al (2021) conducted an in-depth study on the nature of soft X-ray excess and variability of this source by using the multi-epoch XMM-Newton observation data. The results show that the soft X-ray excess of the source is most likely to be originated by the relativistically smeared reflection scenario.…”
Section: Excess Variance Spectramentioning
confidence: 99%
“…For NLSy1s, which occupy extreme physical parameters, most of the current research is dedicated to individual sources with extremely significant and special variability, such as Mrk 335, I Zw 1, and PG 1148+273 (see e.g. Wilkins & Gallo 2015;Ding et al 2021;Wilkins et al 2021). These studies have successfully revealed that the corona of NLSy1s is highly dynamic and that the structure of the corona undergoes significant changes in a short time (such as a few weeks to several years), resulting in extreme multi-band variation and even X-ray-weak special characteristics.…”
Section: Introductionmentioning
confidence: 99%